Utilization of garlic and maize wastes supplemented with olive mill waste water for Pleurotus ostreatus cultivation - Lechner, Bernardo Ernesto (2011)
Garlic and maize cultivations in Argentina are located in similar areas where olive is produced, an advantage for eliminating wastes produced for oil extraction by mushroom cultivation. The aim of this study was to investigate the use of different percentages of olive mill waste water (OMWW) mixed with garlic and maize wastes for the production of Pleurotus ostreatus basidiomes. Strain BAFC 2067 of P. ostreatus was cultivated in garlic and maize wastes mixed with 15, 30, 45 and 60% of OMWW. Bags with 0% OMWW (control) and 100% OMWW were also inoculated. The time of colonization and the yields obtained permitted us to conclude that the best substrate utilized for basidiomes production was a mixture composed of OMWW and maize wastes. The negative effect in the growth of P. ostreatus on garlic wetted with tap water was reverted when garlic wastes contained 15 and 30 % of OMWW. A deleterious effect on yield was observed when 60 % OMWW was utilized for wetting garlic and maize wastes.